Efficiency Based Measures of Inequality - Costel Andonie; Christoph Kuzmics; Brian W. Rogers (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
How should we make value judgments about wealth inequality? Harsanyi (1953) proposes to take an individual who evaluates her well-being by expected utility and ask her to evaluate the wealth possibilities ex-ante (i.e. before she finds her place in society, i.e., under the "veil of ignorance" of Rawls (1971)) assuming that she will be allocated any one of the possible wealth levels with equal probability. We propose a different notion of how wealth levels are allocated, based on a competition or contest. We find that inequality can be captured through the equilibrium properties of such a game. We connect the inequality measures so derived to existing measures of inequality, and demonstrate the conditions under which they satisfy the received key axioms of inequality measures (anonymity, homogeneity and the Pigou-Dalton transfer principle). Our approach also provides a natural way to discuss the tradeoff between greater total wealth and greater inequality.
Keywords: C72; C73; D63; D72; 330; utilitarianism; inequality; contests